Anomalous dielectric relaxation in reduced LiNbO3 single crystals - Kim, CD; Joo, GT; Kim, HG (JAPAN SOC APPLIED PHYSICS, 1997)
Reduced black LiNbO3 single crystals were prepared by heat treatment at 1000 degrees C for 3h in H-2-N-2 atmosphere. The dependence of their dielectric properties on frequency and temperature was investigated from 1kHz to 100kHz in the temperature range 400 degrees C < T < 800 degrees C. A dielectric anomaly was found within 500 degrees C < T < 680 degrees C. The position of the maximum dielectric constant depends on heating rates in air. At a constant heating rate, intensity of dielectric constant depends on the frequency but its position does not change. The anomalous dielectric relaxation resulted from the oxygen vacancies in reduced LiNbO3.
Keywords: LITHIUM-NIOBATE; DEFECT STRUCTURE